Preparation method and application of LDH-induced M-coated N-CNT bifunctional electrocatalyst

Through the LDH-induced dual-function electrocatalyst, the problem of slow kinetics of zinc-space battery catalysts in oxygen reduction and oxygen evolution reactions is solved, and efficient charge and discharge performance and cycle stability is achieved, cost reduction is reduced, and it is better than commercial precious metal catalysts.

CN119725568AActive Publication Date: 2025-03-28XIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411900708.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing zinc-vacuum battery catalysts have slow kinetics in oxygen reduction and oxygen evolution reactions, resulting in low battery charging and discharging efficiency, large energy loss, and high cost, making it difficult to meet the needs of the commercialization process.

Method used

Two-dimensional ultrathin LDH nanosheets were prepared by co-precipitation method and liquid phase peeling method using LDH-induced M@N-CNT dual-function electrocatalyst, and LDH-ZIF-8 composite material was synthesized by in-situ growth method. After thermal activation treatment, the M@N-CNT nanotube dual-function catalyst was catalyzed to optimize its ORR/OER electrocatalytic activity in alkaline systems.

Benefits of technology

It realizes the efficient OER and ORR activity of catalysts in zinc-empty batteries, improves the charging and discharging performance and cycle stability of the battery, and has a lower cost, which is better than commercial precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725568A_ABST
    Figure CN119725568A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an LDH-induced M (at) N-CNT bifunctional electrocatalyst, a two-dimensional ultrathin LDH nanosheet is prepared by adopting a coprecipitation method and a liquid phase stripping method, and an LDH-ZIF-8 composite material is synthesized through an in-situ growth method by changing the variety and proportion of metal ions and adjusting the variety of metal ions of a laminate and the structure of the laminate. The preparation method comprises the following steps: preparing an M-coated N-CNT bifunctional electrocatalyst, further performing high-temperature pyrolysis treatment on the M-coated N-CNT bifunctional electrocatalyst, catalyzing growth of the M-coated N-CNT bifunctional electrocatalyst by using LDH as a sacrificial template agent, optimizing synthesis conditions, so that the obtained M-coated N-CNT bifunctional electrocatalyst is rich in high-density ORR / OER bifunctional catalytic active sites, and the catalyst can obtain a hierarchical porous structure with a high specific surface area; according to the present invention, the ORR / OER catalytic activity comparable with the commercial noble metal catalyst Pt / C and IrO2 can be obtained, and the good cycle stability is provided, such that the zinc-air battery has the high power density and the long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc-air battery catalysts, and in particular to a preparation method and application of an LDH-induced M@N-CNT bifunctional electrocatalyst. Background Art

[0002] Rechargeable metal-air batteries have attracted widespread attention due to their low cost, environmental friendliness, and high safety performance. Among them, rechargeable zinc-air batteries have become the most promising new energy battery for the next generation due to their high specific energy density. Their theoretical energy density is 1086kWh kg -1 , which is 2-5 times that of current lithium-ion battery technology.

[0003] Generally speaking, the catalyst layer of a zinc-air battery largely determines the performance of the entire battery system. Developing efficient bifunctional ORR / OER catalysts to address the sluggish kinetics of oxygen in the oxygen reduction and evolution reactions, thereby improving the battery's charge and discharge efficiency and reducing energy loss, plays a key role in promoting the commercialization of zinc-air batteries. Furthermore, efforts are underway to identify non-precious metal catalytic materials to reduce the cost of zinc-air battery catalysts.

[0004] To date, significant progress has been made in the development of bifunctional non-precious metal catalysts, including transition metal compound materials (oxides, chalcogenides, nitrides, and carbides), heteroatom-doped carbon nanomaterials, and composites composed of both. However, the mechanisms and reaction kinetics of ORR and OER vary between different catalyst materials and electrolytes. Therefore, the catalytic mechanism of bifunctional non-precious metal catalysts remains unclear, and their stability still does not meet the requirements, greatly limiting the cycle life of zinc-air batteries.

[0005] Layered double hydroxides (LDHs) are a class of anionic clay minerals with a structure similar to brucite, consisting of metal hydroxide main layers composed of two or more metal elements and interlayered anions and water molecules. LDHs exhibit promising applications in secondary batteries and electrocatalysis due to their low cost, simple synthesis, easily tunable composition (such as the type and ratio of metal ions in the layers and the type of anions), easily tailored structure (such as the number of layers and interlayer spacing), and ease of functionalization through composites with other materials. While LDHs exhibit excellent OER performance, they lack high-performance ORR active sites and exhibit poor conductivity.

[0006] Zeolitic Imidazolate Frameworks (ZIFs) are a class of metal-organic framework materials with a zeolite framework structure. ZIFs-derived Fe-NC catalysts are considered to be very promising ORR electrocatalysts, but their OER catalytic activity is general and their stability is insufficient. Summary of the Invention

[0007] In view of this, the present invention proposes a method for preparing an LDH-induced M@N-CNT bifunctional electrocatalyst and its application. The two-dimensional ultrathin LDH nanosheets are prepared by co-precipitation and liquid phase exfoliation methods. By changing the type and ratio of metal ions, the type of metal ions in the layer and the layer structure are adjusted. The LDH-ZIF-8 composite material is synthesized by an in situ growth method, which is further subjected to thermal activation treatment. LDH is used as a sacrificial template to catalyze the growth of M@N-CNT nanotube bifunctional catalysts. By optimizing the synthesis conditions, the electrocatalytic activity of the catalyst for ORR / OER in an alkaline system is regulated. The prepared bifunctional catalyst is used to assemble a rechargeable zinc-air battery. Using the catalyst as the positive electrode material, the battery exhibits excellent charge and discharge performance and cycle stability that are superior to commercial catalysts.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing an LDH-induced M@N-CNT bifunctional electrocatalyst comprises the following steps:

[0010] Step 1, Preparation of two-dimensional ultrathin LDH nanosheets

[0011] Step 1.1, adding an aqueous solution containing metal ions to a formamide solution and magnetically stirring the solution, while adding potassium hydroxide solution dropwise to the solution to ensure that the pH value of the solution is maintained at 8-12 and the reaction is continued;

[0012] Step 1.2, cooling the reaction solution obtained in step 1.1 to room temperature, and collecting the generated LDH nanosheets by centrifugation;

[0013] Step 1.3, washing the LDH nanosheets obtained in step 1.2 with a mixed solvent of ethanol and water, and keeping the LDH nanosheets in a wet state for subsequent use;

[0014] Step 2, preparation of LDH@ZIF-8

[0015] The LDH nanosheets, ferric nitrate nine hydrate, and zinc nitrate hexahydrate prepared in step 1 were completely dissolved in methanol, recorded as solution A; 2-methylimidazole was weighed and dissolved in methanol, recorded as solution B; then solution A and solution B were evenly mixed, sealed, and subjected to magnetic stirring for reaction. After the reaction was completed, the mixture was cooled to room temperature, and the product was collected using a high-speed centrifuge, washed with anhydrous ethanol, vacuum dried, and finally ground to obtain powdered LDH@ZIF-8;

[0016] Step 3, preparation of catalyst M@N-CNT

[0017] The LDH@ZIF-8 prepared in step 2 was placed in a clean quartz boat and placed in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. After natural cooling, the pyrolysis product was ground to obtain the final powder material, which was recorded as M@N-CNT.

[0018] Furthermore, in step 1.1, the metal ions are from any two of nickel nitrate hexahydrate, iron nitrate nonahydrate, and cobalt nitrate hexahydrate, and the ratio of the metal ions is 1:1-3:1.

[0019] Furthermore, in step 1.1, magnetic stirring is performed at 20-80° C., and the reaction is continued for 10-60 minutes.

[0020] Furthermore, in the two-dimensional ultrathin LDH nanosheets prepared in step 1, LDH is one of NiFe-LDH, NiCo-LDH, and CoFe-LDH.

[0021] Furthermore, the specific method of step 2 is as follows: the LDH nanosheets, ferric nitrate nine hydrate and zinc nitrate hexahydrate prepared in step 1 are completely dissolved in 300-900 mL of methanol, recorded as liquid A; 2-methylimidazole is weighed and dissolved in 300-900 mL of methanol, recorded as liquid B; then liquid A and liquid B are mixed evenly, sealed, and reacted with magnetic stirring at 20-60°C for 12-36 hours. After the reaction is completed, it is cooled to room temperature, collected using a high-speed centrifuge, washed with anhydrous ethanol three times, and then vacuum dried at 40-80°C for 10-24 hours. Finally, it is ground to obtain powder LDH@Fe-ZIF-8.

[0022] Furthermore, in step 3, the pyrolysis conditions are: under nitrogen atmosphere, a heating rate of 5-10°C / min, and keeping at 800-1200°C for 1-3h.

[0023] Furthermore, in the M@N-CNT bifunctional electrocatalyst prepared in step 3, M is Ni, Fe, Co or binary alloy particles thereof.

[0024] The M@N-CNT bifunctional electrocatalyst prepared according to the above-mentioned LDH-induced M@N-CNT bifunctional electrocatalyst preparation method is used to assemble a rechargeable zinc-air battery, and the M@N-CNT bifunctional electrocatalyst is used as a positive electrode material.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The LDH-induced M@N-CNT bifunctional electrocatalyst has M as an efficient OER active site and retains the efficient ORR active site of the MNC catalyst, and also gives it a large specific surface area, which enables the material to exhibit excellent discharge performance in zinc-air batteries.

[0027] 2. The metal particles in situ generated by LDH in the LDH-induced M@N-CNT bifunctional electrocatalyst promote the growth of carbon nanotubes and improve the degree of graphitization of the catalyst, enabling it to have both bifunctional catalytic activity and exhibit good cycling stability in zinc-air batteries.

[0028] 3. The LDH-induced M@N-CNT bifunctional electrocatalyst prepared in this invention has better ORR and OER activity / stability than commercial precious metal catalysts under alkaline conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a TEM image of the M@N-CNT bifunctional electrocatalyst prepared in Example 1 of the present invention;

[0030] Figure 2 CV graph of the M@N-CNT bifunctional electrocatalyst prepared in Example 1 of the present invention;

[0031] Figure 3 This is the SCV diagram of the M@N-CNT bifunctional electrocatalyst for ORR prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0033] A method for preparing an LDH-induced M@N-CNT bifunctional electrocatalyst comprises the following steps:

[0034] Step 1, Preparation of two-dimensional ultrathin LDH nanosheets

[0035] Step 1.1, adding an aqueous solution containing metal ions to a formamide solution and magnetically stirring at 20-80° C., while adding potassium hydroxide solution dropwise to the solution to ensure that the pH value of the solution is maintained at 8-12, and continuing the reaction for 10-60 minutes, wherein the metal ions are selected from any two of nickel nitrate hexahydrate, iron nitrate nonahydrate, and cobalt nitrate hexahydrate, and the metal ion ratio is 1:1-3:1;

[0036] Step 1.2, cooling the reaction solution obtained in step 1.1 to room temperature, and collecting the generated LDH nanosheets by centrifugation, where the LDH is one of NiFe-LDH, NiCo-LDH, and CoFe-LDH;

[0037] Step 1.3, washing the LDH nanosheets obtained in step 1.2 with a mixed solvent of ethanol and water, and keeping the LDH nanosheets in a wet state for subsequent use;

[0038] Step 2, preparation of LDH@ZIF-8

[0039] The LDH nanosheets, ferric nitrate nine hydrate and zinc nitrate hexahydrate prepared in step 1 were completely dissolved in 300-900 mL of methanol, recorded as solution A; 2-methylimidazole was weighed and dissolved in 300-900 mL of methanol, recorded as solution B; then solution A and solution B were evenly mixed, sealed, and reacted with magnetic stirring at 20-60°C for 12-36 hours. After the reaction was completed, it was cooled to room temperature, and the product was collected by high-speed centrifuge, washed with anhydrous ethanol three times, and vacuum dried at 40-80°C for 10-24 hours. Finally, it was ground to obtain powder LDH@ZIF-8;

[0040] Step 3, preparation of catalyst M@N-CNT

[0041] The LDH@ZIF-8 prepared in step 2 was placed in a clean quartz boat and placed in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions were as follows: under a nitrogen atmosphere, a heating rate of 5-10°C / min, and a heat preservation period of 1-3 hours at 800-1200°C. After natural cooling, the pyrolysis product was ground to obtain a final powder material designated as M@N-CNT. In the prepared M@N-CNT bifunctional electrocatalyst, M is Ni, Fe, Co, or a binary alloy particle thereof.

[0042] Example 1

[0043] Step 1: Add 20 mL of an aqueous solution containing 0.218 g of nickel nitrate hexahydrate and 0.101 g of ferric nitrate nonahydrate to 20 mL of a 23 vol% formamide solution. Magnetic stirring is performed at 80°C, and at the same time, 50 mL of a 0.25 mol·L -1Potassium hydroxide solution was added to ensure that the pH of the solution remained around 10, and the reaction was continued for 10 minutes. After the reaction solution was cooled to room temperature, the generated NiFe-LDH nanosheets were collected by centrifugation. Subsequently, the NiFe-LDH nanosheets were washed three times with a mixed solvent of ethanol and water (volume ratio of 1:1) and kept in a wet state for subsequent use.

[0044] Step 2: Take a certain amount of NiFe-LDH nanosheets, 0.178g of ferric nitrate ninehydrate and 3.39g of zinc nitrate hexahydrate and completely dissolve them in 600mL of methanol, recorded as liquid A; weigh 3.94g of 2-methylimidazole and dissolve it in 600mL of methanol, recorded as liquid B; then mix liquid A and liquid B evenly, seal, and react with magnetic stirring at 60°C for 24h. After the reaction is completed, cool to room temperature, collect using a high-speed centrifuge, wash with anhydrous ethanol three times, and vacuum dry at 60°C for 10h. Finally, grind to obtain powder NiFe-LDH@Fe-ZIF-8.

[0045] Step 3: Weigh a portion of the NiFe-LDH@Fe-ZIF-8 prepared in step 2 and place it in a clean quartz boat, and place it in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions are: nitrogen atmosphere, heating rate of 5°C / min, keeping at 1100°C for 1h, cooling naturally, and grinding the pyrolysis product. The final powder material is recorded as NiFe@N-CNT, and its transmission electron microscope image is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared catalyst is a uniform carbon tube.

[0046] The NiFe@N-CNT bifunctional catalyst was electrochemically tested in a three-electrode electrolytic cell, and the CV obtained was as follows: Figure 2 As shown, from Figure 2 It can be seen that the catalyst has an obvious oxygen reduction peak.

[0047] Figure 3 This is the SCV diagram of NiFe@N-CNT bifunctional catalyst for ORR. The SCV test window is 1.1-0V (vs. RHE), the potential increment is 0.05V, the sampling width is 15s, and the standing time is 300s. Figure 3 It can be seen that the half-wave potential of NiFe@N-CNT for ORR is 0.884 V.

[0048] The catalyst was tested at a current density of 10 mA cm -2 The overpotential of OER was 0.304 V, and the battery was further assembled into a zinc-air battery to test its charge and discharge performance. The open circuit potential was 1.42 V, and the maximum power density was 127.1 mW cm -2, the charge and discharge current density is 10mAcm -1 Under the conditions of , the cycle stability is better than that of precious metal catalysts Pt / C+IrO2.

[0049] Example 2

[0050] Step 1: Add 20 mL of an aqueous solution containing 0.218 g of cobalt nitrate hexahydrate and 0.101 g of ferric nitrate nonahydrate to 20 mL of a 23 vol% formamide solution. While stirring magnetically at 80°C, add 50 mL of a 0.25 mol·L -1 Potassium hydroxide solution was added to ensure that the pH of the solution remained around 10, and the reaction was continued for 10 minutes. After the reaction solution was cooled to room temperature, the generated CoFe-LDH nanosheets were collected by centrifugation. Subsequently, the CoFe-LDH nanosheets were washed three times with a mixed solvent of ethanol and water (volume ratio of 1:1) and kept in a wet state for subsequent use.

[0051] Step 2: Take a certain amount of CoFe-LDH nanosheets, 0.178g of ferric nitrate nine hydrate and 3.39g of zinc nitrate hexahydrate and completely dissolve them in 600mL of methanol, recorded as liquid A; weigh 3.94g of 2-methylimidazole and dissolve it in 600mL of methanol, recorded as liquid B; then mix liquid A and liquid B evenly, seal, and react with magnetic stirring at 60°C for 24h. After the reaction is completed, cool to room temperature, collect using a high-speed centrifuge, wash with anhydrous ethanol three times, and vacuum dry at 60°C for 10h. Finally, grind to obtain powder CoFe-LDH@Fe-ZIF-8.

[0052] Step 3: Weigh a portion of the CoFe-LDH@Fe-ZIF-8 prepared in step 2 and place it in a clean quartz boat, which is then placed in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions are: nitrogen atmosphere, heating rate of 5°C / min, keeping at 1100°C for 1h, cooling naturally, and grinding the pyrolysis product. The obtained catalyst is recorded as CoFe@N-CNT.

[0053] In this embodiment, the half-wave potential of CoFe@N-CNT for ORR is 0.876 V. -2 The overpotential of OER was 0.314 V, and the battery was further assembled into a zinc-air battery to test its charge and discharge performance. The open circuit potential was 1.43 V, and the maximum power density was 115.6 mW cm -2 , the charge and discharge current density is 10mAcm -1 Under the conditions of , the cycle stability is better than that of precious metal catalysts Pt / C+IrO2.

[0054] Example 3

[0055] Step 1: Add 20 mL of an aqueous solution containing 0.436 g of nickel nitrate hexahydrate and 0.051 g of ferric nitrate nonahydrate to 20 mL of a 23 vol% formamide solution. While stirring magnetically at 80°C, add 50 mL of a 0.25 mol·L -1 Potassium hydroxide solution was added to ensure that the pH value of the solution remained around 10, and the reaction was continued for 30 minutes. After the reaction solution was cooled to room temperature, the resulting product, Ni2Fe-LDH, was collected by centrifugation. Subsequently, the product was washed three times with a mixed solvent of ethanol and water (volume ratio of 1:1) and kept in a wet state for subsequent use.

[0056] Step 2: Take a certain amount of Ni2Fe-LDH nanosheets, 0.178g of ferric nitrate ninehydrate and 3.39g of zinc nitrate hexahydrate and completely dissolve them in 600mL of methanol, recorded as liquid A; weigh 3.94g of 2-methylimidazole and dissolve it in 600mL of methanol, recorded as liquid B; then mix liquid A and liquid B evenly, seal, and react with magnetic stirring at 20°C for 36h. After the reaction is completed, cool to room temperature, collect using a high-speed centrifuge, wash with anhydrous ethanol three times, and vacuum dry at 60°C for 10h. Finally, grind to obtain powder Ni2Fe-LDH@Fe-ZIF-8.

[0057] Step 3, weigh a portion of the Ni2Fe-LDH@Fe-ZIF-8 prepared in step 2 and place it in a clean quartz boat, and place it in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions are: under a nitrogen atmosphere, a heating rate of 5°C / min, keeping warm at 1200°C for 1h, cooling naturally, and grinding the pyrolysis product. The final powder material obtained is recorded as Ni2Fe@N-CNT.

[0058] Example 4

[0059] Step 1: Add 20 mL of an aqueous solution containing 0.218 g of nickel nitrate hexahydrate and 0.101 g of ferric nitrate nonahydrate to 20 mL of a 23 vol% formamide solution. Magnetic stirring is performed at 60°C, and at the same time, 50 mL of a 0.25 mol·L -1 Potassium hydroxide solution was added to ensure that the pH value of the solution remained around 10, and the reaction was continued for 30 minutes. After the reaction solution was cooled to room temperature, the generated NiFe-LDH nanosheets were collected by centrifugation. Subsequently, the NiFe-LDH nanosheets were washed three times with a mixed solvent of ethanol and water (volume ratio of 1:1) and kept in a wet state for subsequent use.

[0060] Step 2: Take a certain amount of NiFe-LDH nanosheets, 0.178g of ferric nitrate ninehydrate and 3.39g of zinc nitrate hexahydrate and completely dissolve them in 600mL of methanol, recorded as liquid A; weigh 3.94g of 2-methylimidazole and dissolve it in 600mL of methanol, recorded as liquid B; then mix liquid A and liquid B evenly, seal, and react with magnetic stirring at 40°C for 24h. After the reaction is completed, cool to room temperature, collect using a high-speed centrifuge, wash with anhydrous ethanol three times, and vacuum dry at 80°C for 12h. Finally, grind to obtain powder NiFe-LDH@Fe-ZIF-8.

[0061] Step 3, weigh a portion of the NiCo-LDH@Fe-ZIF-8 prepared in step 2 and place it in a clean quartz boat, and place it in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions are: under a nitrogen atmosphere, a heating rate of 10°C / min, keeping warm at 800°C for 3h, cooling naturally, and grinding the pyrolysis product. The final powder material obtained is recorded as NiFe@N-CNT.

[0062] Example 5

[0063] Step 1: Add 20 mL of an aqueous solution containing 0.218 g of nickel nitrate hexahydrate and 0.218 g of cobalt nitrate hexahydrate to 20 mL of a 23 vol% formamide solution. Magnetic stirring is performed at 20°C, and at the same time, 50 mL of a 0.25 mol·L -1 Potassium hydroxide solution was added to ensure that the pH of the solution remained around 10, and the reaction was continued for 60 minutes. After the reaction solution was cooled to room temperature, the generated NiCo-LDH nanosheets were collected by centrifugation. Subsequently, the NiCo-LDH nanosheets were washed three times with a mixed solvent of ethanol and water (volume ratio of 1:1) and kept in a wet state for subsequent use.

[0064] Step 2: Take a certain amount of NiCo-LDH nanosheets, 0.178g of ferric nitrate ninehydrate and 3.39g of zinc nitrate hexahydrate and completely dissolve them in 600mL of methanol, recorded as liquid A; weigh 3.94g of 2-methylimidazole and dissolve it in 600mL of methanol, recorded as liquid B; then mix liquid A and liquid B evenly, seal, and react with magnetic stirring at 60°C for 12h. After the reaction is completed, cool to room temperature, collect using a high-speed centrifuge, wash with anhydrous ethanol three times, and vacuum dry at 40°C for 24h. Finally, grind to obtain powder NiCo-LDH@Fe-ZIF-8.

[0065] Step 3: Weigh a portion of the NiCo-LDH@Fe-ZIF-8 prepared in step 2 and place it in a clean quartz boat, and place it in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. The pyrolysis conditions are: nitrogen atmosphere, heating rate of 10°C / min, keeping at 1000°C for 2h, cooling naturally, and grinding the pyrolysis product. The final powder material obtained is recorded as NiCo@N-CNT.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst, characterized in that: The specific steps include: Step 1, Preparation of two-dimensional ultrathin LDH nanosheets Step 1.1, adding an aqueous solution containing metal ions into a formamide solution for magnetic stirring, and at the same time, adding a potassium hydroxide solution dropwise into the solution to ensure that the pH value of the solution is maintained at 8-12 and the reaction is continued; Step 1.2, cooling the reaction solution obtained in step 1.1 to room temperature, and collecting the generated LDH nanosheets by centrifugation; Step 1.3, washing the LDH nanosheets obtained in step 1.2 with a mixed solvent of ethanol and water, and keeping the LDH nanosheets in a wet state for subsequent use; Step 2, preparation of LDH@ZIF-8 The LDH nanosheets, iron nitrate nine hydrate and zinc nitrate hexahydrate prepared in step 1 are completely dissolved in methanol, which is recorded as liquid A; 2-methylimidazole is weighed and dissolved in methanol, which is recorded as liquid B; then liquid A and liquid B are evenly mixed, sealed, and reacted with magnetic stirring. After the reaction is completed, it is cooled to room temperature, the product is collected by a high-speed centrifuge, and the product is washed with anhydrous ethanol, vacuum dried, and finally ground to obtain powder LDH@ZIF-8; Step 3, Preparation of Catalyst M@N-CNT The LDH@ZIF-8 prepared in step 2 is placed in a clean quartz boat, and placed in a tubular high-temperature atmosphere furnace for high-temperature pyrolysis. After natural cooling, the pyrolysis product is ground, and the final powder material obtained is recorded as M@N-CNT.

2. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: In step 1.1, the metal ions are any two of nickel nitrate hexahydrate, iron nitrate nonahydrate, and cobalt nitrate hexahydrate, and the ratio of the metal ions is 1:1-3:

1.

3. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: In step 1.1, magnetic stirring is performed at 20-80° C., and the reaction time is continued for 10-60 min.

4. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: In the two-dimensional ultrathin LDH nanosheet prepared in step 1, LDH is one of NiFe-LDH, NiCo-LDH, and CoFe-LDH.

5. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: The specific method of step 2 is as follows: the LDH nanosheets, ferric nitrate nonahydrate and zinc nitrate hexahydrate prepared in step 1 are completely dissolved in 300-900 mL of methanol, recorded as liquid A; 2-methylimidazole is weighed and dissolved in 300-900 mL of methanol, recorded as liquid B; then liquid A and liquid B are mixed evenly, sealed, and reacted with magnetic stirring at 20-60° C. for 12-36 hours. After the reaction is completed, it is cooled to room temperature, collected by a high-speed centrifuge, washed 3 times with anhydrous ethanol, and then vacuum dried at 40-80° C. for 10-24 hours, and finally ground to obtain powder LDH@Fe-ZIF-8.

6. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: In step 3, the pyrolysis conditions are: under nitrogen atmosphere, the heating rate is 5-10°C / min, and the temperature is kept at 800-1200°C for 1-3h.

7. The method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to claim 1, characterized in that: In the M@N-CNT bifunctional electrocatalyst prepared in step 3, M is Ni, Fe, Co or their binary alloy particles.

8. The M@N-CNT bifunctional electrocatalyst prepared by the method for preparing a LDH-induced M@N-CNT bifunctional electrocatalyst according to any one of claims 1 to 7 is characterized in that: The M@N-CNT bifunctional electrocatalyst is used to assemble a rechargeable zinc-air battery, and the M@N-CNT bifunctional electrocatalyst is used as the positive electrode material.

Citation Information

Patent Citations

  • NiFe-LDH / Co-CNTs nano composite material and preparation method and application thereof

    CN113113615A

  • Preparation method of Fe (Ni)-NCNTs (at) NiFe-LDH in-situ electrode

    CN114792810A